Profitability Antecedents of Sharia Life Insurance Companies - Alifia Nur Afiifah; Anniza Citra Prajasari (FEBI UIN Sunan Kalijaga, 2022)
This study aims to determine the effect of internal company factors on the profitability of sharia life insurance companies. The sampling technique used was purposive sampling with the object of research being sharia life insurance companies registered with the Financial Services Authority between 2017-2020. The analysis technique used is multiple linear regression analysis using the Stata 24 application. The results show that partially investment returns have a significant positive effect, and claims have a significant negative effect on profitability. Meanwhile, the premium growth ratio, liquidity and risk based capital are not significant in influencing profitability